Contraceptive Services Available to Unmarried Sexually Active Adolescents - Budiharsana, Meiwita (UI Scholars Hub, 2017)
Background: Low contraceptive use amongst unmarried sexually active young men and women presents an ethical dilemma in Indonesia, particularly in realising reproductive rights as a fundamental human right. This study aims to address the difficulties in extending access to family planning for unmarried sexually active youths. Methods: A review of the laws relating to the provision of family planning was combined with a secondary data analysis of the 2012 Indonesian Demographic Health Survey throughout 6 provinces on the island of Java. The sample population included 5,150 unmarried adolescents, aged 15 to 24 years. The 2012 Indonesian Demographic Health Survey was the first and only survey that included unmarried young women in Indonesia. The association between subjects who had 'ever had sex' and three groups of predictors (demographic characteristics, peer influences, and knowledge of contraceptive methods) were examined using multivariate logistic regressions. Results: Results of the study found that subjects who were unmarried but had engaged in sexual activity were more likely to be those aged 19 to 21 years (OR = 2.36) and 22 to 24 years (OR = 6.81), of low education status (OR = 2.1), with a boyfriend or girlfriend (OR = 2.38), and those who approved of pre-marital sex (OR = 8.5). Conclusions: Results from this research suggest that new interpretations of the Law 52/2009 regarding family planning and Law 36/2009 that prohibits health services to unmarried sexually active youths are required in order to address the issues faced by Indonesia's youth